Analysis and Design of Data Warehouse at Bank M - Agus Anwar; Danan Pradipta; Sri Aryani (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2018)
Banking has a very strategic role in supporting therunning of the economy and national development considering itsfunction as an intermediary institution, payment transactionorganizer, and monetary policy transmission tool. The bankingindustry, data warehouse is something that is very importantexistence, because with this data warehouse, performanceanalysis of a bank will be much easier to do. The HOLAP methodof data warehouse banking processing can present the desiredinformation quickly. With the support of data warehouses,corporate leaders can be more helpful in making decisions fasterand more precise.